Weight gain and enteric methane production of cattle fed on tropical grasses - Korir, Daniel; Marquardt, Svenja; Eckard, Richard; Sánchez, Andrea C.; Dickhoefer, Uta; Merbold, Lutz; Butterbach-Bahl, Klaus; Jones, Christopher S.; Robertson-Dean, M.; Goopy, John P. (Commonwealth Scientific and Industrial Research Organisation, 2023)
Context: Planted grasses are becoming an increasingly important feed resource for tropical smallholder ruminant production; yet, limited research has been conducted to quantify productivity or enteric methane (CH4) production of animals consuming these grasses.